Alveolar macrophages are essential for protection from respiratory failure and associated morbidity following influenza virus infection. - Christoph Schneider; Samuel P Nobs; Alex K Heer; Michael Kurrer; Glynis Klinke; Nico van Rooijen; Johannes Vogel; Manfred Kopf (PLoS Pathogens)
Alveolar macrophages (AM) are critical for defense against bacterial and fungal infections. However, a definitive role of AM in viral infections remains unclear. We here report that AM play a key role in survival to influenza and vaccinia virus infection by maintaining lung function and thereby protecting from asphyxiation. Absence of AM in GM-CSF-deficient (Csf2-/-) mice or selective AM depletion in wild-type mice resulted in impaired gas exchange and fatal hypoxia associated with severe morbidity to influenza virus infection, while viral clearance was affected moderately. Virus-induced morbidity was far more severe in Csf2-/- mice lacking AM, as compared to Batf3-deficient mice lacking CD8α+ and CD103+ DCs. Csf2-/- mice showed intact anti-viral CD8+ T cell responses despite slightly impaired CD103+ DC development. Importantly, selective reconstitution of AM development in Csf2rb-/- mice by neonatal transfer of wild-type AM progenitors prevented severe morbidity and mortality, demonstrating that absence of AM alone is responsible for disease severity in mice lacking GM-CSF or its receptor. In addition, CD11c-Cre/Ppargfl/fl mice with a defect in AM but normal adaptive immunity showed increased morbidity and lung failure to influenza virus. Taken together, our results suggest a superior role of AM compared to CD103+ DCs in protection from acute influenza and vaccinia virus infection-induced morbidity and mortality.